2019
DOI: 10.1177/0021998319884101
|View full text |Cite
|
Sign up to set email alerts
|

Temperature variation during continuous laser-assisted adjacent hoop winding of type-IV pressure vessels: An experimental analysis

Abstract: Laser-assisted tape winding is an automated process to produce tubular or tube-like continuous fiber-reinforced polymer composites by winding a tape around a mandrel or liner. Placing additional layers on a previously heated substrate and variation in material and process parameters causes a variation in the bonding temperature of fiber-reinforced thermoplastic tapes which need to be understood and described well in order to have a reliable manufacturing process. In order to quantify the variation in this crit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(38 citation statements)
references
References 30 publications
0
30
0
Order By: Relevance
“…The maximum and minimum variation in substrate and tape temperatures among the three winding experiments was found to be 80 • C for layer-22 and 10 • C for layer-7, respectively. The possible reasons for the variations in the temperature measurements within three rings production could be related to the local variation in material properties of the prepreg [44], local deconsolidation in the heated region and varying emissivity coefficient as a function of temperature [19] which was constant in the current configuration of the thermal camera.…”
Section: Temperature Measurementsmentioning
confidence: 99%
See 1 more Smart Citation
“…The maximum and minimum variation in substrate and tape temperatures among the three winding experiments was found to be 80 • C for layer-22 and 10 • C for layer-7, respectively. The possible reasons for the variations in the temperature measurements within three rings production could be related to the local variation in material properties of the prepreg [44], local deconsolidation in the heated region and varying emissivity coefficient as a function of temperature [19] which was constant in the current configuration of the thermal camera.…”
Section: Temperature Measurementsmentioning
confidence: 99%
“…The ATW technique is highly automated and used to manufacture tubular-like structures such as flywheel rotors [21,38], tanks for energy storage, pipes for oil and gas industry [29,44], tubes for bikes, etc. The heating source can be a hot gas torch [12,13,22], infrared lamp [4,16,18], near-infrared (NIR) diode lasers [5,10,11,31], and recently LED heating [25].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have focused on monitoring the temperature during AFP or ATW processes where multiple tapes are deposited on top of each other [9,11,22,[35][36][37]. However, the critical analysis of the adjacent AFP/ATW process of fiber-reinforced polymer composites has received less attention in the literature.…”
Section: Nomenclature C Pmentioning
confidence: 99%
“…The wound product will be cured and demolded to become the final product. Studies have shown that the process parameters during the winding process, such as heating temperature, tape tension and roller pressure and winding speed have a significant effect on the mechanical property of the composite wound products [12][13][14][15][16][17]. As an important index to characterize the mechanical properties of wound products, hoop tensile strength is employed to reflect the ability of composite cylindrical parts to resist hoop tensile failure.…”
Section: Introductionmentioning
confidence: 99%
“…In Nath's article [14], four control factors machine speed, roller pressure, tape tension and tape temperature were investigated for the tape winding process. Meanwhile, processing temperature, winding speed and compaction pressure were selected as the key parameters to study for tape winding process according to Dai et al [15] and Zaami et al [16]. However, three parameters including tape tension, roller pressure and temperature were analyzed for developing a NC tape winding machine from a research of Shi et al [17].…”
Section: Introductionmentioning
confidence: 99%